(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: The non-nutritive habit of thumb sucking, which is common in youngsters, has drawn attention to orthodontics and pediatric dentistry because of its possible effects on dental occlusion and the formation of an anterior open bite in preschool-aged children. When the back teeth come into contact with the upper and lower front teeth, there is no vertical overlap, a condition known as an anterior open bite. Various nations, including Hilla City, Dhaka, Bangladesh, and Saveetha, have conducted numerous studies. The purpose of these studies is to evaluate thumb sucking on the anterior open bite in children’s preschool. Methods: This cross-sectional survey was carried out in Saudi Arabia from July to November 2024. The purpose of this study was to assess the prevalence of anterior open bite in children between the ages of three and five, as well as its association with harmful oral practices. Males and females in the Saudi population between the ages of three and five were the inclusion criteria, while men and females older than six were the exclusion criteria. Results: The study involved 722 children, revealing a mean age of 4.9 years and a slight male predominance (54.6%). A significant 64.8% of participants exhibited thumb sucking habits, potentially affecting their dental and psychological health. Most children began thumb sucking between ages 1 to 3, with 41.5% sustained this habit for over six months, which correlated with dental misalignments, as nearly equal proportions of maxillary anterior proclination (49.1%) and mandibular anterior retroclination (51.7%) were observed. Notably, only 42.3% sought dental advice, indicating a gap in preventive care. Additionally, significant relationships were found between maxillary anterior tooth proclination and factors such as gender, age, parental age, and socioeconomic status, with p-values indicating strong statistical significance (all p < 0.01). Conclusion: the study revealed the significant prevalence of thumb sucking, observed in 64.8% of the 722 preschool-aged children assessed, indicating a prominent behavioral trend that warrants attention from dental professionals. The findings revealed a clear correlation between prolonged thumb sucking and the development of anterior open bite, with a notable 49.1% of children showing maxillary anterior proclination and 51.7% demonstrating mandibular anterior retroclination, both of which are recognized dental misalignments. Given that 41.5% of participants sustained the thumb sucking habit for over six months, the risk of malocclusion is amplified, underscoring the importance of early intervention and parental awareness. Moreover, only 42.3% of the children sought dental advice, signalling a critical gap in preventive care that could mitigate long-term dental complications.